Pengaruh Disiplin Kerja terhadap Kinerja Pegawai dengan Lingkungan Kerja sebagai Variabel Intervening pada Kantor Bupati Bulukumba - Aru Faradiba Akbar; Chalid.Imran Musa; Rezky Amalia Hamka; Widhi Nugraha Sumiharja Darmawinata; Anang Setiawan (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2026)
This study aims to analyze the influence of work discipline on employee performance with the work environment as an intervening variable at the Regent Office of Bulukumba. The main focus of this study is to identify the direct and indirect effects among work discipline, work environment, and employee performance, as well as to examine the mediating role of the work environment in the relationship between work discipline and employee performance. This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 67 employees of the Regent Office of Bulukumba. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS software to examine the relationships among variables and the mediating effect of the work environment. The results indicate that work discipline has a positive and significant effect on employee performance, work discipline has a positive and significant effect on the work environment, the work environment has a positive and significant effect on employee performance, and work discipline has a positive and significant effect on employee performance through the work environment as an intervening variable at the Regent Office of Bulukumba. These findings suggest that improving work discipline, supported by a conducive work environment, can enhance employee performance optimally.